On-Treatment Blood Pressure and Cardiovascular Outcomes in Older Adults With Isolated Systolic Hypertension. Issue 2 (February 2017) - Yano, Yuichiro; Rakugi, Hiromi; Bakris, George L.; Lloyd-Jones, Donald M.; Oparil, Suzanne; Saruta, Takao; Shimada, Kazuyuki; Matsuoka, Hiroaki; Imai, Yutaka; Ogihara, Toshio
Abstract : Our aim was to assess optimal on-treatment blood pressure (BP) at which cardiovascular disease (CVD) and all-cause mortality risks are minimized in Japanese older adults with isolated systolic hypertension. We used data from the VALISH study (Valsartan in Elderly Isolated Systolic Hypertension) that recruited older adults (n=3035; mean age, 76 years) with systolic BP (SBP) of ≥160 mm Hg and diastolic BP of <90 mm Hg. Patients were treated by valsartan. Patients were also categorized into 3 groups based on achieved on-treatment SBP of <130 mm Hg (n=317), 130 to <145 mm Hg (n=2025), or ≥145 mm Hg (n=693). The primary outcome was composite CVD (coronary heart disease, stroke, heart failure, cardiovascular deaths, other vascular diseases, and kidney diseases) with secondary outcome being all-cause mortality. Cox proportional hazards models were used to assess the CVD risk for each group. Over a median 3-year follow-up (8022 person-years), 93 CVD events and 52 deaths occurred. Using the on-treatment SBP of 130 to <145 mm Hg as reference stratum, the multivariable-adjusted hazard ratios and 95% confidence intervals of CVD and all-cause mortality risks for those with SBP<130 mm Hg were 2.08 (1.12–3.83) and 2.09 (0.93–4.71) and for those with SBP≥145 mm Hg were 2.29 (1.44–3.62) and 2.51 (1.35–4.66), respectively. On-treatment diastolic BP yielded no relationships with CVD or all-cause mortality risk. In conclusion, among Japanese older adults with isolated systolic hypertension, SBP in the range between 130 and 144 mm Hg was associated with minimal adverse outcomes and a reduction in CVD and all-cause mortality. The BP range will need to be confirmed in randomized controlled trials. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00151229. Abstract : Supplemental Digital Content is available in the text.